REVITALISASI KEARIFAN LOKAL DALAM PENDIDIKAN KARAKTER MULTIKULTURAL: KERANGKA CERPEN-GRAM SEBAGAI SCAFFOLDING INTEGRASI GLS-PPK DI SEKOLAH DASAR - Khoeri Abdul Muid; Su'ad; Santoso (JISPE Journal of Islamic Primary Education, 2024)
Indonesia, as a multicultural country, faces challenges in integrating local wisdom into contextual, systematic, and meaningful character education. This study aims to develop and validate the Multicultural Gram-Short Story Framework (CM) as a structured scaffolding for internalizing local wisdom-based values ​​in the School Literacy Movement (GLS) and Character Education Strengthening (PPK) programs. The approach used is Conceptual Developmental Research (CDR) with four phases: theory and policy exploration, creative methodological adaptation, model design, and empirical validation in homogeneous elementary schools in Pati Regency. The results indicate that CM functions as a “value simulator,” helping students understand and reflect on cultural diversity contextually despite being in a homogeneous environment. A limited trial showed a significant increase in students’ multicultural character scores (p < 0.001) with Cohen’s d = 1.90 considered very large compared to similar studies (e.g., Gojali, 2017; qualitative d ≈ 1.0). However, these results should be interpreted with caution because this study is a preliminary validation study. This research contributes to three domains: (1) Theoretical, through the integration of character theory (Lickona), scaffolding (Vygotsky), and ethnopedagogy; (2) Methodological, through the cross-domain adaptation of Shortpen-Gram into a value analysis tool; and (3) Practical, in the form of a Literacy Pocket Book (BUSALI) media that combines literary literacy and character education in the context of GLS PPK.